Innovación en las empresas manufactureras del Estado de Michoacán - González Garcilazo, Martha Atzimba (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
In Mexico, the companies that carry out Research and Development (R & D) are few; They are at a disadvantage to the demand for goods with higher quality and governed by regulations demanded by global markets. The Michoacan companies face a great challenge, recognizing the innovators. This research, whose objective is to determine the extent to which the variables Business structure, culture, technological capacity, financial economy and business linkage affect the innovation of the manufacturing companies of the State of Michoacán, is transeccional correlacional- causal. Based on the above, a questionnaire was generated, validated and applied to identify the incidence of the variables in 203 manufacturing companies of the State of Michoacán; obtaining the correlation of the variables, from the Spearman correlation and the Factorial Analysis, which allows accepting the model. The main companies identified for this research focus on the knowledge of innovation in the companies surveyed, the lack of support to governments for innovation and dissemination; In addition to a current database of manufacturing companies in the region. Keywords: Innovation, business structure, culture, technological capacity, human talent, financial capacity and business linkage.

En México, las empresas que realizan Investigación y Desarrollo (I+D) son pocas; se encuentran en desventaja a la demanda de bienes con mayor calidad y regidas por normativas que exigen los mercados globales. Las empresas michoacanas enfrentan un gran reto, reconocerse potencialmente innovadoras. Esta investigación, cuyo objetivo es determinar en qué medida las variables Estructura Empresarial, Cultura, Capacidad Tecnológica, Talento Humano, Capacidad Financiera, y Vinculación Empresarial inciden en la innovación de las empresas manufactureras del Estado de Michoacán, es de carácter transeccional-correlacional-causal. Con base en lo anterior, se generó, validó y aplicó un cuestionario para identificar la incidencia de las variables mencionadas en 203 empresas manufactureras del Estado de Michoacán; obteniendo correlación significativamente baja de todas las variables, a partir de la correlación de Spearman y el Análisis Factorial, lo que permite aceptar el modelo. Las principales limitantes identificadas para esta investigación se enfocan en el desconocimiento del verdadero sentido de la innovación en las empresas encuestadas, la falta de apoyo gubernamental para innovar y su difusión; además de una base de datos vigente de las empresas manufactureras de la región.
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-D-2019-0211; Cultura; Capacidad tecnológica; Talento humano; Capacidad financiera; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1084